Synthesis and material characterization of calcium carbonate (CaCO3) from the waste of chicken eggshells. Issue 1 (1st February 2022) - Ningrum, R A; Humaidi, S; Sihotang, S; Bonardo, D; Estananto
Abstract: Synthesis and basic characterization of calcium carbonate (CaCO3 ) material produced from the extraction of chicken egg shells is proposed. The studied method is applied for the basic analysis of the mineral CaCO3 in the field of membrane materials. Three basic characteristics of CaCO3 have been investigated, namely microstructure, crystal structure and vibrational modes. Microstructure were measured using a scanning electron microscope (SEM), while crystal structure were measured using an X-ray diffractometer (XRD). Fourier transform infra-red (FTIR) spectroscopies were used to determine the vibrational modes. Experimental results show that the morphology of the sample has the characteristics of a microstructure with a mean grain size of 3 μm, the morphology of the resulting microstructure has a loose spacing between grains so as to provide an empty space between the sample grains. The crystal structure of CaCO3 formed is trigonal and has a crystal size of 53.306 nm, indicating the formation of nano crystals in the sample, while the FTIR spectroscopies data show the appearance of the three highest peaks at wave numbers of 3637 cm −1, 1438 cm −1, and 871 cm −1, which indicates the OH strain functional groups in Ca(OH)2, CO and calcite groups, respectively. Several studies also reported that the hydroxyl and carbonation groups at similar wave numbers were 3643 cm −1, 1445 cm −1 and 877 cm −1, and at 712 cm −1, 876 cm −1, and 1425 cm −1 which correspond to C=C, CO, and CS vibrations.